Determinants of Ethnic or Geographical Differences in Infectivity and Transmissibility of Helicobacter pylori. (1st April 1999) - Fallone, Carlo A
Abstract : The prevalence of Helicobacter pylori infection is variable in different countries. There are two distinct patterns of H pylori prevalence with respect to age depending on the geographical region studied. The first pattern is widespread infection early in childhood with elevated prevalence rates of close to 80% throughout adulthood, and the second is increasing prevalence with age. This variability in pattern suggests a difference in infectivity or transmissibility of H pylori infection. Potential determinants of these differences are reviewed including environmental, bacterial and host factors. The most important determinant is likely socioeconomic class, which affects living conditions and sanitation, thus altering exposure to the bacterium. Host factors also play a role, perhaps via host receptors for H pylori . Bacterial factors may also contribute, although compelling evidence is lacking.